2015
DOI: 10.1021/acs.jpclett.5b02015
|View full text |Cite
|
Sign up to set email alerts
|

Ligand Surface Chemistry Dictates Light Emission from Nanocrystals

Abstract: There are several contradictory accounts of the changes to the emissive behavior of semiconductor nanocrystal upon a ligand exchange from trioctylphosphine/cadmium-phosphonates passivation to N-butylamine. This communication explains the contradictory accounts of this reaction using new insights into ligand chemistry. Also, a previously unknown link between surface emission and cadmium-phosphonate (Z-type) ligands is shown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 32 publications
(88 reference statements)
2
39
0
Order By: Relevance
“…Figure a shows the surface‐to‐core ratios of the integrated areas of the PL as a function of temperature. It was observed that the ratio increased monotonically as the temperature dropped to 80 K. We have previously explained this phenomenon in terms of a thermodynamic equilibrium of carriers in the core and the surface states . Lower temperatures, thus, favor the occupancy of the surface state, which is lower in energy than the core state .…”
Section: Figurementioning
confidence: 95%
“…Figure a shows the surface‐to‐core ratios of the integrated areas of the PL as a function of temperature. It was observed that the ratio increased monotonically as the temperature dropped to 80 K. We have previously explained this phenomenon in terms of a thermodynamic equilibrium of carriers in the core and the surface states . Lower temperatures, thus, favor the occupancy of the surface state, which is lower in energy than the core state .…”
Section: Figurementioning
confidence: 95%
“…The addition of a ligand having a molecular structure suitable for the desired purposes into QDs is particularly important in QD applications. However, ligand addition via an exchange process tends to decrease the PLQY of QDs. One method of ligand exchange is to add the desired ligand by replacing an X-type ligand with an L-type ligand that provides an electron pair. Although this is an energetically favorable reaction, it causes broad surface emission and has the disadvantage of lowering the PLQY of QDs. ,, There is also a method of synthesizing a QD with a specific X-type ligand and then substituting the ligand with another X-type ligand that is desired; a carboxylic acid on the surface of the QD can be replaced with another carboxylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…The amine ligands, such as small organic amines, are capable to coordinate to unpassivated surface cadmium sites. [28][29][30][31][32] XPS analysis revealed that the coordination between amino groups of PEI and surface cadmium of CdSe occurs. This results in two obvious PL spectral changes.…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%
“…First, the unpassivated surface cadmium sites are considered as nonradiative electron traps. [29] Please do not adjust margins…”
Section: Materials Advances Accepted Manuscriptmentioning
confidence: 99%